Anaplastic Multiple Myeloma- a Morphological Challenge – A Case Series - Sakthisankari, S; Kumar, Prasanna N; Syed, Tabbu (Indian Journal of Medical and Paediatric Oncology, 2020)
Anaplastic multiple myeloma (AMM) is a rare and aggressive variant of plasma cell neoplasm. It is relatively treatment resistant when compared to conventional myeloma. It can arise de novo or transform from a preexisting plasma cell myeloma. Morphologically, AMM is recognized by the presence of immature plasma cells and pleomorphic, multilobated cells. Here, we present three cases of AMM.
Keywords: Anaplastic myeloma; anaplastic variant of multiple myeloma; bizarre plasma cells; multilobated plasma cells